Cold cereal - Rex, Adam. (New York : Balzer + Bray, 2012)
A boy who may be part changeling, twins involved in a bizarre secret experiment, and a clurichaun in a red tracksuit try to save the world from an evil cereal company whose ultimate goal is world domination.
Keywords: Cereals, Prepared -- Juvenile fiction; Magic -- Juvenile fiction; Adventure stories; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction